Wrinkled1 Accelerates Flowering and Regulates Lipid Homeostasis between Oil Accumulation and Membrane Lipid Anabolism in Brassica napus - Li, Qing; Shao, Jianhua; Tang, Shaohua; Shen, Qingwen; Wang, Tiehu; Chen, Wenling; Hong, Yueyun (Frontiers in Plant Science, 2015)
Wrinkled1 (WRI1) belongs to the APETALA2 transcription factor family; it is unique to plants and is a central regulator of oil synthesis in Arabidopsis. The effects of WRI1 on comprehensive lipid metabolism and plant development were unknown, especially in crop plants. This study found that BnWRI1 in Brassica napus accelerated flowering and enhanced oil accumulation in both seeds and leaves without leading to a visible growth inhibition. BnWRI1 decreased storage carbohydrates and increased soluble sugars to facilitate the carbon flux to lipid anabolism. BnWRI1 is localized to the nucleus and directly binds to the AW-box at proximal upstream regions of genes involved in fatty acid synthesis and lipid assembly. The overexpression (OE) of BnWRI1 resulted in the up-regulation of genes involved in glycolysis, fatty acid synthesis, lipid assembly, and flowering. Lipid profiling revealed increased galactolipid monogalactosyldiacylglycerol (MGDG), digalactosyldiacylglycerol (DGDG), and phosphatidylcholine (PC) in the leaves of OE plants, whereas it exhibited a reduced level of the galactolipids DGDG and MGDG and increased levels of PC, phosphatidylethanolamide (PE), and oil (triacylglycerol, TAG) in the siliques of OE plants during the early seed development stage. These results suggest that BnWRI1 is important for homeostasis among TAG, membrane lipids and sugars, and thus facilitates flowering and oil accumulation in B. napus.